Indian and Chinese immigrant communities : comparative perspectives / edited by Jayati Bhattacharya and Coonoor Kripalani. - Bhattacharya, Jayati; Kripalani, Coonoor; Bose, Sugata 1956- (Anthem-ISEAS India-China studies, 2015)
"This interdisciplinary collection of essays offers a window onto the overseas Indian and Chinese communities in Asia. Contributors discuss the interactive role of the cultural and religious 'other', the diasporic absorption of local beliefs and customs, and the practical business networks and operational mechanisms unique to these communities. Growing out of an international workshop organized by the Institute of Southeast Asian Studies in Singapore and the Centre of Asian Studies at the University of Hong Kong, this volume explores material, cultural and imaginative features of the immigrant communities and brings together these two important communities within a comparative framework"-- Provided by publisher.